Ejido organization, ecotourism, and governance. The experience of El Palmito, Concordia, Sinaloa, Mexico - Corona Álvarez, Lidia Guadalupe (2024)
In the socio-cultural sustainability framework, preserving cultural diversity and promoting sustainable development in Latin American communities is imperative. This study aimed to identify and document the ejido organisation, government structures, and ecotourism practices in the ejido El Palmito, Concordia, Sinaloa, Mexico. The methodological design was exploratory descriptive in scope from a qualitative perspective, supported by the hermeneutical paradigm and the case study, direct observation, literature review and three semi-structured interviews with committee members. The main findings testified that the ejido organisation contributes to preserving natural resources and decision-making, and its various actions are planned around ecotourism. Governance was distinguished by collective equity in that members are bearers of voice and vote, the union-type solid collaboration networks within the committee, and outstanding bridge-type relationships and links with other non-governmental organisations. The viability of sustainable tourism practices in rural areas and strengthening community ties, traditions and cultural practices were evidenced. The study expanded the scientific knowledge of a sparsely researched area.